2022
DOI: 10.1073/pnas.2113871119
|View full text |Cite
|
Sign up to set email alerts
|

Rad54 and Rdh54 prevent Srs2-mediated disruption of Rad51 presynaptic filaments

Abstract: Srs2 is a superfamily 1 (SF1) helicase that participates in several pathways necessary for the repair of damaged DNA. Srs2 regulates formation of early homologous recombination (HR) intermediates by actively removing the recombinase Rad51 from single-stranded DNA (ssDNA). It is not known whether and how Srs2 itself is down-regulated to allow for timely HR progression. Rad54 and Rdh54 are two closely related superfamily 2 (SF2) motor proteins that promote the formation of Rad51-dependent recombination intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 85 publications
2
13
0
Order By: Relevance
“…Physical conflicts between the myriad of proteins present on DNA limit its accessibility and can impede the successful repair of damage during HR. Specific examples of this include the inhibition of Sgs1 translocation by Rad52 [52], the inhibition of Srs2 translocation by Rad54 and Rdh54 [42], and the inhibition of both Srs2 and Sgs1 by the meiosis specific recombinase Dmc1 [53]. Our data indicates that Rdh54 acts as a barrier to Rad54 at newly formed D-loop intermediates, consistent with previous studies that showed Rdh54 limited D-loop size [54].…”
Section: Rdh54 Blocks Rad54 Activity At Newly Formed D-loop Intermedi...supporting
confidence: 89%
See 3 more Smart Citations
“…Physical conflicts between the myriad of proteins present on DNA limit its accessibility and can impede the successful repair of damage during HR. Specific examples of this include the inhibition of Sgs1 translocation by Rad52 [52], the inhibition of Srs2 translocation by Rad54 and Rdh54 [42], and the inhibition of both Srs2 and Sgs1 by the meiosis specific recombinase Dmc1 [53]. Our data indicates that Rdh54 acts as a barrier to Rad54 at newly formed D-loop intermediates, consistent with previous studies that showed Rdh54 limited D-loop size [54].…”
Section: Rdh54 Blocks Rad54 Activity At Newly Formed D-loop Intermedi...supporting
confidence: 89%
“…Rad54 is thought to remove Rad51 by induced ATP hydrolysis of Rad51 in a mechanism resembling the activity of RecA [5, 15, 55, 56]. In contrast, Rdh54 has previously been reported to stabilize Rad51-ssDNA filaments [42], although the exact mechanism is unclear. Several possibilities include the stabilization of Rad51 against ATP hydrolysis [42], the physical interference of Rad54 translocation, or by limiting Rad54 movement through the interaction between Rdh54 and Rad51.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A set of mediator proteins (in budding yeast, Rad52, Rad55 and Rad57) enable Rad51 to assemble into a nucleoprotein filament on the single-stranded ends of a DSB that are created by 5' to 3' resection (15,(22)(23)(24). Rad51's ability to promote DNA strand exchange also depends on the Rad54 chromatin remodeler, which binds to Rad51 and promotes strand invasion into homologous sequences and later branch migration steps in recombination (25)(26)(27)(28)(29). In contrast, meiotic recombination in many eukaryotes, including both budding yeast and mammals, recombination depends on Dmc1, a Rad51 paralog (19,30).…”
Section: Introductionmentioning
confidence: 99%